Association between nutritional status, physical fitness and executive functions in preadolescents: A person-centered approach - Zhu, Yuxin; Sun, Fenghua; Tao, Sisi; Cooper, Simon B.; Gao, Tian-Yu (Frontiers in Pediatrics, 2022)
Objective: In the current study, a person-centered approach was adopted to investigate the relationship between nutritional status and physical fitness profiles and executive functions (EF) in preadolescents. Methods: Participants (Mage = 10.8 yrs; Male = 50.8%) were recruited from two primary schools in Hong Kong. Nutritional status (body mass index [BMI]), physical fitness including cardiorespiratory fitness (CRF, predicted VO2max, multi-stage fitness test) and speed-agility (20-m sprint) were measured on school days. EF performance was measured using the Flanker task (inhibition) and the Sternberg task (working memory). Results: Data from 120 preadolescents were considered valid. Three distinct profiles were identified by a person-centered approach. Profile 1 was featured by high BMI (21.61±3.38 kg/m2), poor VO2max (33.29±23.96 ml/kg/min), and slow 20-m sprint (4.51±0.13 sec). Profile 2 was featured by low BMI (15.99±3.38), fair VO2max (44.98±23.96) and fast 20-m sprint (3.97±0.13). Profile 3 was featured by low BMI (15.63±3.38), poor VO2max (32.37±23.96), and slow 20-m sprint (4.48±0.13). Wald chi-square test revealed preadolescents in profile 1 and profile 2 performed better than profile 3 in accuracy of Flanker task (1 vs. 3: χ2 = 12.23, P < 0.001; 2 vs. 3: χ2 = 10.86, P = 0.001). That is, for normal weight preadolescents with poor CRF and speed-agility, those with superior nutritional status performed better in inhibition. For normal weight preadolescents with poor nutritional status, those with superior CRF and speed-agility had better inhibitory capacity. Conclusion: Compared to the commonly used variable-centered approach, this person-centered approach is a valuable addition that expands the understanding of the association between nutritional status, physical fitness and EF in preadolescents. Results are discussed with regards to maximizing health behaviors and implications for educational policy.